Report of the end of project workshop - Kisauzi, T.; Mayanja, S.; Kisauzi, Dan; Naziri, D. (2016)
This report provides a synthesis of the workshop proceedings to share ENDURE project results with stakeholders, build a consensus on project achievements and chart a way forward. The workshop was attended by participants representing various stakeholders including donor/funding agencies, national and international research organizations and universities; implementing partners, private sector players and farmers.